TEMA SENTRAL DALAM PEMIKIRAN JEAN PAUL SARTRE - Syukri, Ahmad (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2019)
Sartre's philosophical thinking was a reaction to the situation in the first and second world wars, which he considered a humanist. The order of life oriented to materialism and idealism. humans are only considered objects, as 'parts' in large machines called societies and countries. .the relationship between humans and their environment becomes very formal, their thinking is based on profit and loss, everything that does not bring use / productive is considered to be worthless. Sartre's thinking offers a way of liberation by re-enlivening the conversation about human values, by opening up new possibilities that are better for the future life of humans. sartre again directed his analysis to the main problem about who is human who has freedom, independence and as an autonomous personal being.